2016
DOI: 10.1016/j.ajur.2015.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Prostatic sarcoma of the Ewing family in a 33-year-old male – A case report and review of the literature

Abstract: Ewing sarcoma is the second most common primary bone tumor seen in children and adolescents, typically presenting between 10 and 20 years of age. Extraosseous sarcomas of the Ewing family in adults are rare. We report a manifestation of this tumor entity in the periprostatic tissue of a 33-year-old male and discuss our treatment approach. Transrectal biopsy is a feasible and simple diagnostic tool for unclear pelvic masses. Multi-modal therapy and central registries are needed to gain knowledge of rare pelvic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…ES usually affects the bone of children and young adults, but it can also arise in older patients and localize in extraskeletal sites, mainly in soft tissues ( 1 ). A review of the English-language literature revealed that the urogenital tract is rarely involved: the most common site is the kidney, with almost 200 cases described ( 7 , 8 ), followed by the bladder ( 9 ), and the prostate ( 10 , 11 ). Ureteral localization is an exceptional finding, with only four cases of primary ES of the ureter previously reported ( 12 15 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ES usually affects the bone of children and young adults, but it can also arise in older patients and localize in extraskeletal sites, mainly in soft tissues ( 1 ). A review of the English-language literature revealed that the urogenital tract is rarely involved: the most common site is the kidney, with almost 200 cases described ( 7 , 8 ), followed by the bladder ( 9 ), and the prostate ( 10 , 11 ). Ureteral localization is an exceptional finding, with only four cases of primary ES of the ureter previously reported ( 12 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…ES usually affects bone, but it can also localize in extraskeletal sites, most commonly in soft tissues (12% of cases) (1). Urogenital tract involvement is a rare event, most frequently arising in the kidney, followed by the bladder and the prostate (7)(8)(9)(10)(11). As for the ureter, a primary ES is an exceptional finding: to our knowledge, there are no more than four cases described in the literature (12-15).…”
Section: Introductionmentioning
confidence: 99%
“…The survival rate of these patients was 2 to 12 mo. The treatment strategy included surgery and adjuvant and neoadjuvant chemotherapy, but there was limited data acquisition[13].…”
Section: Discussionmentioning
confidence: 99%